A simplified dynamic zone model for a probabilistic assessment of hygrothermal risks in building components. (October 2017) - Tijskens, Astrid; Janssen, Hans; Roels, Staf
Abstract: Most building component simulation software simplify the interior boundary conditions; only the temperature and relative humidity can be assigned. However, when performing a probabilistic assessment of the hygrothermal risks, a wider range of realistic indoor boundary conditions can be desired, and more indoor climate parameters need to be implemented. Instead of combining with a complex BES-model, an integrated simplified dynamic zone model is proposed, developed to expand the functionality of DELPHIN 5.8. In this zone model, the original interior boundary conditions are replaced by a fictive air layer, representing the indoor zone and thus the indoor conditions to which the building component is exposed. The air layer, in turn, is subjected to equivalent boundary conditions. Through these equivalent boundary conditions and air layer properties, the indoor climate parameters are taken into account. Hence, this model enables to assess a broader variety of interior climates.